Optimization of the Four-Wheel Patrol of Samapta Units in Preventing the Crime of Motor Vehicle Theft in the Jurisdiction of the Tegal Police - Pesat Gatra Vedattama, I Dewa Putu Marcello (Indonesian Journal of Police Studies, 2024)
The Tegal Police Samapta Unit is the spearhead of preventive police action in preventing criminal acts from occurring within the jurisdiction of the Tegal Police. In the implementation of the Tegal Police Samapta Four-wheeled Patrol Unit, several deficiencies were found in terms of planning, organizing, implementing, and monitoring and not following the Patrol SOP stipulated in Perkabaharkam Number 1 of 2017 concerning Patrols. The author’s final project raises the issue of "Why is the performance of the Samapta Four-wheeled Patrol Unit to prevent theft in the Tegal Police jurisdiction not yet optimal?" The method used is the Tegal Police’s four-wheeled patrol unit. This study used a qualitative approach with the type of field research by conducting limited observations, interviewing informants, and studying documents. In addition, the data used was also obtained from various references such as articles, journal books, and relevant online media news. This study uses management theory and SWOT theory as well as three concepts that are relevant to the problem, namely, the optimization concept, theft concept, and the patrol concept based on Perkabaharkam Number 1 of 2017 concerning Patrols. In addition, some factors influenced both internally and externally, implementing the Tegal Police’s four-wheeled patrol units unable to be carried out optimally. With this problem, there are still very many deficiencies that must be addressed both in terms of human resources or personnel and the methods used. Later research is expected that the development of criminal acts of curator in the jurisdiction of the Tegal Police can decrease.